2006
DOI: 10.12693/aphyspola.110.605
|View full text |Cite
|
Sign up to set email alerts
|

Positron Scattering on Atoms and Molecules in the Limit of Low Energy

Abstract: Starting from experimental cross-sections for positron scattering in argon and nitrogen, we examine different energy ranges. In the zero-energy limit the cross-section falls with energy and can be described by modified effective range theory for polarization potential. In a few eV range the cross-sections are constant vs. energy. As far as it is possible to force the elastic scattering phase shifts in a way that both experimental differential cross-sections are reproduced and the total cross-section remains co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…direct annihilation and formation processes. The comprehension of these elastic and inelastic processes may be very useful in the near future to create alternative techniques of producing positron beams (to cite positron-molecule collisions is a controversial area and several considerations have been discussed [5][6][7][8][9][10][11][12]). A suitable theoretical method should be capable of dealing with several important aspects of the problem such as polarization effects, resonances, electronically inelastic scattering with several open and closed channels, positronium formation and, if possible, with computer codes applicable to targets in general.…”
Section: Introductionmentioning
confidence: 99%
“…direct annihilation and formation processes. The comprehension of these elastic and inelastic processes may be very useful in the near future to create alternative techniques of producing positron beams (to cite positron-molecule collisions is a controversial area and several considerations have been discussed [5][6][7][8][9][10][11][12]). A suitable theoretical method should be capable of dealing with several important aspects of the problem such as polarization effects, resonances, electronically inelastic scattering with several open and closed channels, positronium formation and, if possible, with computer codes applicable to targets in general.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in more detailed study [10] we showed that the atomic radii dea e-mail: kamil@fizyka.umk.pl termined from positron scattering data using a classical rigid sphere model are comparable to covalent radii of atoms. However this simple picture does not translate directly into the quantum mechanics since pure quantummechanical hard-sphere model is not applicable to lowenergy positron scattering [11].…”
Section: Introductionmentioning
confidence: 99%